2013
DOI: 10.3846/16111699.2013.804875
|View full text |Cite
|
Sign up to set email alerts
|

Integration Strategies for the Success of Mergers and Acquisitions in Financial Services Companies

Abstract: The research shows how managers can plan a successful integration process following a merger and acquisition. Presents a series of frameworks which discuss understanding value creation in mergers and acquisitions, selecting the right strategy and managing the integration process; drawn largely from research studies and interviews made to managers with experience in leading integration processes of financial services companies in Europe, Latin America and USA. Concludes that, by following the key drivers framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…This is based on the assumption that pre merger shareholders still retained some of their ownership with the HPQ shareholdings. This in line with [18] who found that managers can plan a successful integration process following a merger. On the other hand, Compaq has been witnessing a drop in its P/E ratio during the 1999 to 2000 period, while HP has been experiencing a rather stable P/E ratio during the 1996 to 2000 period.…”
Section: Comparative Analysis Of Eps and P/esupporting
confidence: 62%
“…This is based on the assumption that pre merger shareholders still retained some of their ownership with the HPQ shareholdings. This in line with [18] who found that managers can plan a successful integration process following a merger. On the other hand, Compaq has been witnessing a drop in its P/E ratio during the 1999 to 2000 period, while HP has been experiencing a rather stable P/E ratio during the 1996 to 2000 period.…”
Section: Comparative Analysis Of Eps and P/esupporting
confidence: 62%
“…Regarding firm size, in M&As studies, size is measured by market value (Martin & Shalev, 2017), number of employees (Buehler et al, 2006), total assets (Barros & Dominguez, 2013; Behr & Heid, 2011; Faccio & Masulis, 2005) or total sales (Amihud et al, 1990; Pablo, 2009). In our study, we adopt the definitions based on total sales and total assets adjusted for inflation 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The literature approached the deal completions issue at different angles. For example, Kau, Linck, and Rubin (2008) focus on companies' market returns; Barros and Dominguez (2013) and Dauber (2012) assess post‐merger synergies; Pablo (2009), Rossi and Volpin (2004), Teerikangas (2012) and Wang and Wang (2012) analyse cross‐border determinants; Faccio and Masulis (2005), Gorbenko and Malenko (2014) and Ismail (2011) study the means of payments; Jandik, Lallemand, and McCumber (2017) examine the value‐return relevance of debt issuance for failed takeovers; Branch, Wang, and Yang (2008) focus on the estimation methods; Phalippou, Xu, and Zhao (2015) examine the U.S. M&As with the perspective of neo‐agency theory of takeovers; and Liu (2016) shows that failed takeover attempts in the USA could be “wake‐up calls” for the underperforming managers of target firms. On the other hand, Reddy, Xie, and Huang's (2016) case study analysis shows that the institutional and political background factors exert considerable influence on the completion rates of cross‐border M&As.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not purchases but the union of owners of companies that participate in the merger (Sedlacek & Kuhrova, 2012). The price of target company plays a role only when companies with different (mutually independent) stockholders merge (Barros & Domingues, 2013). The presented research focuses in particular on mergers recorded in the Trade Register (2013) as implemented in the territory of the Czech Republic in the past six years.…”
Section: Figure 2 Tracking Trends In Manda Value Enhancement Over the mentioning
confidence: 99%